Analisis Kestabilan Lubang Bukaan Tail Gate BT-06 Berdasarkan Klasifikasi Geomekanika (RMR-System) Pada Penambangan Bawah Tanah PT. Cahaya Bumi Perdana, Sawahlunto - Fenny Aulia Gustin; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. The excavation of a tunnel through the rock mass causes its balance to be disrupted, hence the rock is unable to support its own load, the ground surrounding the excavation will collapse. Several analytical techniques such Geotechnical analysis which uses the Rock Mass Ratting System can be used to identify the rock mass characteristics in a tunnel. This research would provide findings based on rock mass class, rock strength, safety factor depends on the potential for wedge collapse and ground support recommendations. Based on the weighting obtained by the RMR system analysis, it is found that with a stand up time of 260 hours, the rock mass class is in Class III (fair rock). A safety factor of 16.471 (stable wedge) and 3 potential general joint directions that have the possibility for wedge collapse are obtained on the basis of the processing results (N173 ° E / 76 °, N142 ° E / 24 °, N113 ° E / 28 °).The RMR weighting data analysis suggest that if using rock bolt (20 mm diameter fully grouted) with a length of 4 m and a spacing of 1.5-2 m on the walls and roof then added wire mesh installation, 50-100 mm thick shotcrete on the roof and 30 mm on the wall. Furthermore, if the wooden support is needed, use wood with a diameter of 20 cm, 2 m long and class IV with a spacing of 1.5 m.Keywords: Tunnel, Geotechnical, RMR-System, Safety Factor, Ground Support.